Translating concept into practice : enabling first-year health sciences teachers to blueprint effective flipped learning approaches : final report. - Karanicolas, Sophia; Snelling, Catherine; Winning, Tracey (Australia. Dept of Education and Training (DET), 2018)
The flipped classroom has increasingly become a core model of e-learning in 21st century education. The pedagogy incorporates a group of learning strategies including blended learning, just-in-time teaching and active learning. Contemporary educational research has consistently found that if students have the opportunity to preview key concepts ahead of class time, the face-to-face session can be more effectively used for active learning where concepts are analysed and applied (Herein & Schiller, 2013; Karanicolas & Snelling, 2010; McLaughlin et al., 2014). At the project's completion, 440 university teachers had participated in 22 workshops that used a collegial approach to help participants implement a flipped learning approach in their classrooms. The project website became an ongoing resource for workshop attendees, along with a Facebook group that served as a platform to sustain momentum and provide peer support. Throughout the project presentations and workshops were run at national and international learning and teaching conferences that disseminated outcomes and information about the project. [Executive summary, ed]